Ceiling of the Mahamandapa - Temples of India Project Team (Jio Institute, 2024)
The ceiling of the mahamandapa (pillared hall) rests on eight elaborately carved tall pillars. Each pillar has a square base, transitioning into a shaft that changes from square to octagonal in the middle and finally becomes circular at the top. Above these are architectural moldings, a shaft that supports the capital, and carved bharvahakas (mythical flying load-bearing figures). Notably, the square portion of the shaft of each pillar in the mahamandapa is carved with a niche on each of its four faces. Within these niches are sculptures portraying various figures, including apsaras (celestial damsels), yogis (ascetic), or royal figures in acts of veneration and in one case, a four-armed Bhairav.